The slow exercise tempo during conventional squat elicits higher glycolytic and muscle damage but not the endocrine response - Wilk, Michal; Krzysztofik, Michal; Petr, Miroslav; Zajac, Adam; Stastny, Petr (Neuro endocrinology letters, 2021)
OBJECTIVE: The squat exercise is one of the most exhaustive ones in which different resistance training methods can elicit various changes in the concentration of many metabolites circulating in the blood. Therefore, this study aims to assess the differences between slow (5/0/3/0) and conventional (2/0/2/0) barbell squat movement tempo to concentric failure on acute metabolites and hormonal responses. MATERIALS AND METHODS: Ten experienced powerlifters (24.3 ± 3.2 y; 77.9 ± 7.2 kg; 141 ± 17.5 kg Squat 1RM) who compete at the national and international level performed five sets of the barbell squat exercise (SQ) to failure at load 80% 1RM with two different tempos of movement: a 2/0/2/0 medium tempo (MED) and a 5/0/3/0 slow tempo (SLO) randomly one week apart. Venous blood samples (10ml) were collected from the antecubital vein, to determine acute pre and post-exercise values of testosterone (T), growth hormone (GH), insulin-like growth factor I (IGF-1), cortisol (C), creatine kinase (CK), and lactate acid (LA). RESULTS: The SLO protocol resulted in higher time under tension (p<0.01) and a lower number of performed repetitions (p<0.01) than the MED protocol. Both exercise protocols test showed a high increase of T, C, GH, IGF-1, CK, and LA between pre and post-exercise (p<0.01). Performing 5 sets of SLO squats resulted in a higher post-exercise increase of LA (p < 0.03) and CK (p < 0.02) than MED protocol. There were no other significant differences in analyzed endocrine variables. Therefore, the SLO exercise tempo elicits higher lactate and muscle damage, but not the acute hormonal response. CONCLUSION: This study demonstrated that in terms of endocrine response, the optimal moderate exercise tempo results in a high endocrine response, which is not dramatically increased by a longer time under tension resulting from slow exercise execution. On the other hand, slow speed resulted in a prolonged time under tension, more muscle damage, and lactate production; which may play a large role in stimulating muscle growth and tissue regeneration.
Keywords: Creatine Kinase; Muscles; Lactic Acid; odporový trénink; Insulin-Like Growth Factor I; Muscle, Skeletal; hydrokortison; Exercise; Resistance Training; Hydrocortisone; Growth Hormone; kosterní svaly; kyselina mléčná; insulinu podobný růstový faktor I; lidé; svaly; Humans; Human Growth Hormone; testosteron; kreatinkinasa; lidský růstový hormon; cvičení; Testosterone; růstový hormon